Tax evasion, psychological egoism, and revenue collection performance: Evidence from Amhara region, Ethiopia - Mu, Renyan; Fentaw, Nigatu Mengesha; Zhang, Lu (Frontiers in Psychology, 2023)
Tax evasion is the illegal withholding or underpayment of taxes, typically accomplished by intentionally providing false or no evidence to tax authorities. Tax evasion has had a severe detrimental influence on the economy of the Amhara National Regional State, Ethiopia. The Amhara Regional State lost tax revenue in recent years due to tax evasion. The objective of this study was to see how tax evasion, taxpayers’ psychological egoism, and other relevant factors affect tax revenue collection performance in the Amhara Region, Ethiopia. Data was collected from 395 VAT-registered taxpayers through a structured questionnaire. The structural equation model and multiple regression analyses with SPSS/ AMOS software were utilized for data analysis. This research revealed that tax evasion and psychological egoism negatively affect tax revenue collection performance. Tax education and technology significantly and positively affected tax revenue collection performance. Meanwhile, the relationships between the above factors (tax evasion, tax education, and technology) and the tax revenue collection performance are reliably mediated by taxpayers’ psychological egoism. Those findings can give clues to researchers, tax experts, and policymakers for improving the tax revenue collection performance in Amhara Region. The government can enhance public education to reduce tax evasion and such misbehavior caused by taxpayers’ psychological egoist actions. Meanwhile, the most up-to-date tax invoicing technologies, like artificial intelligence and machine learning technology should be adopted.